Continuing Vocational Training of Employees in Small Enterprises - in the Context of Corporate Social Responsibility - Atanassova, Margarita (Research Papers, 2020)
The increase in the relative share of small enterprises in Bulgaria providing continuing vocational training to employees is analyzed as a positive environment for the future development of socially responsible practices in organizations. The main objective of this study is to study and systematize trends in the dynamics of continuing vocational training for employees in small enterprises in Bulgaria as an EU member and to outline opportunities for increasing their contribution to the development of corporate social responsibility at national, European and global level. The subject of the study are small enterprises and the subject of research is the continuing vocational training of employees in the context of corporate social responsibility. The main information source is the data from the last three periodic surveys of the continuing vocational training of the employees in the enterprises, which is carried out every 5 years according to the Eurostat methodology.JEL:  М1, М5
Keywords: Continuing vocational training; Socially responsible policies; Corporate social responsibility